Exploring the Value of a BioBlitz as a Biodiversity Education Tool in a Post-Secondary Environment - Gass, Susan; Mui, Amy; Manning, Paul; Cray, Heather; Gibson, Lara (Environmental Education Research, 2021)
Biodiversity education is widely considered a necessary component of protecting global biodiversity by helping to change harmful attitudes and actions. BioBlitz events, rapid surveys of all living things in a defined area over a set period, are becoming a widely used practice for biodiversity education. The aim of this study was to evaluate the use of a campus BioBlitz as a place-based experiential learning experience for early undergraduate science students by having students work alongside naturalist experts to build skills in species observation and identification using the iNaturalist app. We surveyed students about their perceptions of the BioBlitz experience. Eighty two percent of students agreed that the BioBlitz provided valuable hands-on learning, they valued learning outside of a traditional classroom, and felt they learned new knowledge about species identification. Many students reported a heightened sense of environmental stewardship and a positive sense of place on campus. We conclude with a discussion of the benefits of a campus BioBlitz in overcoming many of the emerging challenges associated with outdoor field-based education.
Publisher: Routledge
Keywords: Animal Behavior; Biodiversity; Campuses; Climate; Computer Software; Educational Benefits; Environmental Education; Experiential Learning; Foreign Countries; Hands on Science; Identification; Outdoor Education; Place Based Education; Program Descriptions; Science Education; Student Attitudes; Teaching Methods; Undergraduate Students